Exploring the Variation in Levels of Drug-related Violence - Mares, David R. (Revista Brasileira de Estudos de Defesa, 2022)
This article reviews the literature on the relationship between the illegal drug trade and violence. The literature review examines the characteristics and nature of violence in the illegal drug trade, distinguishing its systemic elements from the violence of individuals. There is a growing literature looking at variations in levels of violence; some of these explanations compete, while others could be complementary. We lack an overarching theoretical framework that integrates complementary arguments into a general causal argument. The conclusion discusses is the theoretical, methodological, and empirical challenges to developing a general framework for analyzing violence in the illegal drug trade. A general framework guides analysis across all cases, regardless of region, drug, or level of violence. What differs among empirical cases are the values of the causal variables in the distinct context, not the relationship among those variables; variation in levels of violence is the result of differing values among the causal variables. The conclusion ends by suggesting avenues for research.